Peningkatan Kemampuan Siswa Menulis Narasi Melalui Pendekatan Proses di Sekolah Dasar - Harnon . (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
The learning of writing, particularly writing narratives, at primary schools aims to enable the students to express their ideas and thoughts into narratives. Previous studies inform that the skill of Grade IV students of Primary School 03 Alai Timur, Padang, in writing narrative is less satisfied. This is attributed to the facts that student’s lack of interest in writing and the teacher has no effective strategy in teaching. This research aims to discover the accurate and effective strategy in solving the problem of learning to write narratives at primary schools. The research is conducted to improve primary school students’ skill in writing narratives. This research employs a strategy considered being able to solve the problem of primary school students skill in writing narratives, that is the process approach. The approach is one of the alternatives for problem solution. The data collection techniques employed observation, interviews, and students writing. Then, the data are analyzed through qualitative data analysis model. To keep the data validity, Triangualation technique is used. The research findings indicate that strategy of process approach may improve the skill of Grade IV students of Primary School 03 Alai Timur Padang in writing narratives. Improvement is seen in each phase of learning which includes pre writing, writing and post writing. Assessment approach contributes to improvement of primary school student’s skill in writing narratives. Keywords: students’ ability; learning to write; process approach